Community-Based Hip Screening for Up to Four-Month-Old Infants and Health Guidance for Their Caregivers in Japan: A Nation-Wide Survey - Kyoko Yoshioka-Maeda; Hiroshige Matsumoto; Asa Inagaki-Asano; Chikako Honda (MDPI AG, 2023)
Early detection of developmental dysplasia of the hip (DDH) in children is crucial. Due to COVID-19, maternal and child health services have been suspended temporarily, increasing the risk of late detection of DDH. This study aimed to reveal Japan's current situation regarding community hip screening for newborns and infants and to provide health guidance for caregivers regarding DDH. A web-based, nationwide cross-sectional survey was conducted between February and March 2023 (n = 1737). One public health nurse overseeing maternal and child health per municipality responded to the 2022 municipality hip screening system. Among the 436 municipalities that responded (response rate: 25.1%), 97.5% implemented hip screening within 4 months, and approximately 60% performed it during newborn home visits, while only 2.3% conducted hip ultrasound screening. Perfect checking of the risk factors for DDH during newborn home visits and training opportunities for home visitors must be improved. Educational programs regarding DDH for home visitors and caregivers are needed to prevent the late diagnosis of DDH. Furthermore, collaboration between pediatric orthopedic surgeons and nurses is crucial for developing effective community-based hip-screening systems by bridging the evidence and practice gap in the early detection of DDH.